Systematic review on factors associated with self-perceived burden among cancer patients - Liu, Bingyang; Lee, Khuan; Sun, Chao; Wu, Di; Lim, Poh Ying (Springer, 2022)
Introduction: Cancer is the leading cause of death in the world. There was a high prevalence of high self-perceived burden (SPB) among cancer patients and this could bring adverse consequences to the physical and mental health of cancer patients, which can lead to suicide if not treated well. This review aims to determine the prevalence of SPB among cancer patients and its risk factors. Methods: Published journals before September 2021, from five databases (PubMed, ScienceDirect, Springer, Cochrane, and CNKI) were retrieved according to the keywords. The keywords used included cancer patients, terminally ill patients, cancer, SPB, self-perceived burden, self-burden, self-perceived, factor, predictor, associated factor, determinants, risk factor, prognostic factor, covariate, independent variable, and variable. The quality of the inclusion and exclusion criteria was independently reviewed by three researchers. Results: Out of 12,712 articles, there are 22 studies met the eligibility criteria. The prevalence of SPB among cancer patients ranged from 73.2 to 100% in Malaysia, China, and Canada. Most of them had moderate SPB. Out of the reported factors, age, gender, marital status, ethnicity, residence, educational level, occupational status, family income, primary caregiver, payment methods, disease-related factors, psychological factors, and physical factors were mostly reported across the studies. Conclusions: In conclusion, SPB prevalence is high in cancer patients. Therefore, hospitals, non-governmental organizations, relevant policymakers, and communities can provide special programs for high-risk groups to provide psychological guidance or design corresponding interventions to reduce the SPB level of patients and improve the quality of life.